2000
DOI: 10.1029/1999gl010961
|View full text |Cite
|
Sign up to set email alerts
|

A multiwavelength investigation of the ring effect in the day sky spectrum

Abstract: Abstract. Ring effect refers to the 'filling-in' of the Fraunhofer absorption lines in the day sky spectrum as compared to the solar spectrum. Rotational Raman scattering is believed to be the main cause for this excess in the sky spectrum. Earlier measurements showed contradictory behavior of this effect with solar zenith angle and wavelength. It is important to take proper account of this effect as it otherwise results in overestimating the dayglow emission intensities and underestimating the number densitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 16 publications
3
42
0
Order By: Relevance
“…This also minimizes any potential errors arising from the absorption by O 3 (≈1% peak-to-valley differential absorption for SZA=75 • and 350 DU) or the very weak broad O 4 absorption feature at 343.4 nm (Greenblatt et al, 1990) which cannot be neglected at larger SZA. FI was also measured for eight other Fraunhofer lines between 333.7 and 374.6 nm, and was found to increase with line depth in agreement with other measurements (Pallamraju et al, 2000). Figure 2 shows the day-to-day variation in FI for five mornings in late July where the sky was cloud-free as the sun passed through SZA=40±1 • .…”
Section: Measurement Resultssupporting
confidence: 68%
“…This also minimizes any potential errors arising from the absorption by O 3 (≈1% peak-to-valley differential absorption for SZA=75 • and 350 DU) or the very weak broad O 4 absorption feature at 343.4 nm (Greenblatt et al, 1990) which cannot be neglected at larger SZA. FI was also measured for eight other Fraunhofer lines between 333.7 and 374.6 nm, and was found to increase with line depth in agreement with other measurements (Pallamraju et al, 2000). Figure 2 shows the day-to-day variation in FI for five mornings in late July where the sky was cloud-free as the sun passed through SZA=40±1 • .…”
Section: Measurement Resultssupporting
confidence: 68%
“…Kattawar et al (1981) report a filling-in of 2.5% at 6301.5 Å for a Fe-I line. Brinkmann (1968) calculates a filling-in of about 1.7 in the center to 1.9% in the wings for a hypothetical line at 4000 Å, underlining the continuous and smooth effect across the line profile, which is also measured by Pallamraju et al (2000). Brinkmann (1968) reports observations showing a decrease of the filling-in with wavelength by a factor of 2 between 4383 and 6563 Å, and more recent measurements (Pallamraju et al 2000, Fig.…”
Section: Results From Eq (1) (Method1)mentioning
confidence: 97%
“…The details on the Ring effect variation and the procedure employed for the data reduction to obtain the daytime emissions using HIRISE have been described in detail elsewhere (Pallamraju et al, 2000;2002). In this study we discuss the behavior of observed emission rates on different days, both with and without geomagnetic storm occurrence.…”
Section: Instrumentationmentioning
confidence: 99%
“…The main challenge for the daytime optical measurements is the strong solar background continuum, which is approximately three orders of magnitude brighter than the daytime airglow emissions. At Boston University we have developed a high-resolution (0.12Å at 630.0 nm) imaging echelle spectrograph called the HIRISE (Pallamraju et al, 2002), which has been used to understand the Ring effect variation in the sky spectrum as opposed to the Fraunhofer spectrum (Pallamraju et al, 2000), observations of the sunlit auroral arcs (Pallamraju et al, 2001), and the daytime magnetospheric cusps (Pallamraju et al, 2004) in the OI 630.0 nm emissions.…”
Section: Instrumentationmentioning
confidence: 99%